Implementation of Tahfidz Al-Qur’an Program in Islamic School Curriculum: Integration Models and Their Effectiveness - Wahyudin abdullah; Khuriyah (al-Afkar, Journal For Islamic Studies, 2026)
This research examines the integration models of Tahfidz Al-Quran program in Islamic school curriculum and analyzes their effectiveness. There is a gap between the ideal concept and the implementation of the Tahfidz program, where many Islamic schools implement Tahfidz program without thorough planning, resulting in unsystematic implementation and tending to become an additional burden for students. This research aims to comprehensively analyze various integration models of Tahfidz program into the Islamic school curriculum structure and measure their effectiveness based on previous research. Using the literature review method utilizing the Harzing Publish or Perish version 8 application, this research analyzes relevant publications from 2020-2024. The results show that the implementation of the Tahfidz Al-Quran program in Islamic school curriculum can be realized through three main integration models: curricular, extracurricular, and project-based integration models. The effectiveness of program implementation is influenced by the qualifications of the supervising teachers, the learning methods applied, the evaluation system used, support from the school and family environment, and the consistency of program implementation. This research also identifies seven potential areas for developing more effective Tahfidz programs relevant to contemporary educational demands, including hybrid integration models, comprehensive evaluation frameworks, competency-based approaches, program personalization, adaptive technology integration, program sustainability, and community involvement.